AN ELECTRONIC ART APPROACH IN THE ADAPTATION OF WHITE SPACE ART COMPOSITION ON CHINESE INK PAINTING - Liew, Jia Xi; Wan Jamarul Imran, Wan Abdullah Thani (UNIMAS Publisher, 2023)
White Space Art, otherwise known as Xu Shi, is not only used to create a powerful visual drawing space, but also a key composition principle and aesthetic feature in Chinese Ink Painting. This study focuses on the application of White Space Art in the implementation of the artwork. In other words, which initiatively to explore the method of combining the approach of technology with Chinese Ink Painting Art. Through the practical experience which executed by the author, intently to verify the feasibility if White Space Art to express the space philosophy of electronic art and discusses the possibility that the practical process can be used for further reference. The implementation of such a merger to achieve an artwork in the form of contemporary art which gives a new perception and meaning to the Chinese Ink Painting Art in a new context rather than in a conventional background.